Integrated evaluation of targeted and non‐targeted therapies in a network meta‐analysis. Issue 3 (23rd September 2019) - Proctor, Tanja; Jensen, Katrin; Kieser, Meinhard
Abstract: Individualized therapies for patients with biomarkers are moving more and more into the focus of research interest when developing new treatments. Hereby, the term individualized (or targeted) therapy denotes a treatment specifically developed for biomarker‐positive patients. A network meta‐analysis model for a binary endpoint combining the evidence for a targeted therapy from individual patient data with the evidence for a non‐targeted therapy from aggregate data is presented and investigated. The biomarker status of the patients is either available at patient‐level in individual patient data or at study‐level in aggregate data. Both types of biomarker information have to be included. The evidence synthesis model follows a Bayesian approach and applies a meta‐regression to the studies with aggregate data. In a simulation study, we address three treatment arms, one of them investigating a targeted therapy. The bias and the root‐mean‐square error of the treatment effect estimate for the subgroup of biomarker‐positive patients based on studies with aggregate data are investigated. Thereby, the meta‐regression approach is compared to approaches applying alternative solutions. The regression approach has a surprisingly small bias even in the presence of few studies. By contrast, the root‐mean‐square error is relatively greater. An illustrative example is provided demonstrating implementation of the presented network meta‐analysis model in a clinical setting.